A Provably Secure Proxy Signcryption Scheme Using Bilinear Pairings - Nai-Wei Lo; Jia-Lun Tsai (Journal of Applied Mathematics)
As people in modern societies are busier than any human era and computer network has profound impact on how people work and live through fast and convenient information exchange, people need more help from each other to accomplish more work via network connections in limited period of time. Therefore, privilege delegation mechanism has become a necessary service in modern enterprises and organizations. Proxy signcryption scheme provides a secure privilege delegation mechanism for a person to delegate his privilege to his proxy agent to accomplish things. In 2010, Lin et al. had proposed an efficient signcryption scheme using bilinear pairings. However, we found that the proxy signcryption scheme of Lin et al. is vulnerable to the chosen warrant attack. A provably secure proxy signcryption scheme using bilinear pairings is introduced accordingly. In terms of performance efficiency, the proposed scheme is superior to other existing schemes. In addition, a new security model is proposed to describe proxy signcryption scheme; based on the security model we show that the proposed scheme is provably secure in terms of indistinguishability under adaptive chosen ciphertext attack (IND-CCA2), unforgeability under adaptive chosen message attack (EF-CMA), and unforgeability under adaptive chosen warrant attack (EF-CWA).